Historia i biografia, czyli o trylogii ukraińskiej Józefa Łobodowskiego - Dorota Kielak (Annales Universitatis Paedagogicae Cracoviensis. Studia Historicolitteraria, 2023)
In this paper, the Ukrainian trilogy by Józef Łobodowski has been interpreted as a historical novel, in which the described events took place in the Kuban region in the period between 1918 and 1922. The history of the Bolshevik revolution and the Civil War in the Caucasus area of Russia has been presented in a vivid story, which was inspired by the author’s personal experiences. The protagonist of the trilogy is the author’s own alter ego. The author’s participation in the discussed events significantly influenced the artistic form of the novel. The work possesses the features of a reportage novel, with its inherent verism, a trend towards a faithful depiction of life during the Russian Civil War, as well as elements of journalism that correspond to the writer’s journalistic activity. The reportage characteristics of the trilogy did not hinder the author from complying in his narration with the pattern of Sienkiewicz’s novel W pustyni i w puszczy (In Desert and Wilderness). In this way, the Ukrainian trilogy became a work with an original structure, in which the author also objectified his own emigrational experiences.